Sumatra benzoin (Styrax spp.) - Katz, E.; García Fernandez, C.; Goloubinoff, M. (Routledge, 2002)
Several species of Styrax trees from Sumatra and Indochina produce benzoin resin. This resin is used for incense, perfume and pharmaceutical industries. Formerly, S. benzoin was cultivated in low lands of Palembang and North Sumatra but its importance decreased after 2nd World War. Now, product from S. paralleloneurum Perk that grows in North Sumatra highlands is the most valued. Batak farmers manage benzoin trees in agroforest system. Benzoin gardens recover high biodiversity level when abandoned. In some places these gardens are the only forest cover left. Farmers tap S paralleloneurum between June and September and collect the resin three months later. If done properly, benzoin can be extracted for nearly 60 years. It is necessary to dry the resin before transport because it melts and looses quality. Most of the production is used in Central Java in incense and cigarette manufactures. Only small part is exported to other countries via Singapore. In the 70's income from benzoin was good enough to allow Batak children to study in university. Now prices are less attractive for young farmers. Traditional market is stagnant but new niches can appear.